Protective coating for dental application - Ng, Michelle Hui Xuan (2016)
Initial adhesion of microorganisms to acrylic resin denture is a vital step to their colonization. This phenomenon is dependent on the surface properties of the acrylic resin denture. Therefore, surface modification is of paramount importance to modulate the adhesion of microorganisms. Carboxybetaine methacrylate (CBMA) and sulfobetaine vinylimidazole (SBVI) have demonstrated remarkable antifouling properties. In this study, 1) a single layer coating in different concentration and 2) same concentration with different number of layers of coating using CBMA and SBVI were studied. Surface characteristics were examined to determine the performance of the coatings to minimize the adhesion of microorganisms. Compared to the uncoated control, results had shown a significant increase in hydrophilicity and reduction in roughness in CBMA and SBVI coated acrylic resin samples. Bacterial adhesion test indicated that 2-layer SBVI coating had the best antifouling property with 81% reduction in E. faecalis adhesion compared to the uncoated control. It was also noticed that the performance in E. faecalis adhesion on CBMA and SBVI coating was very different despite their similar hydrophilicity and surface roughness. This implies that the chemical composition of the agents may be a determinant factor for the coating performance in bacterial adhesion.